Phytoplankton Community And Water Quality During Pre And Post Monsoon In The Oman Sea (Part Of Iranian Waters) - Saraji, Fereshteh (2014)
This study was carried out along the Iranian coastal waters of the Oman Sea in 2008 and 2010 during the pre-monsoon and post-monsoon seasons. Samples were collected at 10 transects from coastal to offshore zones and from surface to deep layers. The aims of this study were to determine the spatial and temporal variation of phytoplankton community and water quality. Kajian ini dijalankan di sepanjang perairan pesisir pantai Iran di Laut Oman, dalam tahun 2008 dan 2010, semasa pra- dan pasca musim monsun. Sampel dikutip di 10 transek dari zon pesisir pantai hingga lepas pantai dan dari permukaan hingga lapisan yang lebih dalam. Kajian ini bertujuan menentukan variasi ruang dan masa komuniti fitoplankton dan kualiti air.